Epidemiologic and clinical characteristics of COVID-19 patients admitted in a tertiary care hospital in Khulna city - Haque, Syed Didarul; Kabir, Muhammad Ashraful; Biswas, Prithwy Shankar; Al Amin, Abu Md Mayeenuddin; Ali, Md Barkot; Islam, Baishakhi (Mediscope, 2022)
Background & objective: The outbreak of coronavirus disease 2019 (COVID-19) has become a large threat to global health due to its high contagious nature and varied mortality. The number of infected cases and deaths are rising exponentially all over the world, including Bangladesh. This study aims to investigate the epidemiological and clinical features of COVID-19 patients admitted in Gazi Medical College Hospital (GMCH), Khulna, Bangladesh. Methods: In this study, we included 110 RT-PCR positive COVID-19 cases at GMCH, Khulna, Bangladesh from 1 July, 2021 to 31 August, 2021. Demographic, clinical, laboratory and radiological data of the patients were recorded and analyzed. Results: Among 110 study subjects, 51.8% were male. The mean age was 52.6 years, with majority (43.6%) belonging to the age group of 40-59 years. Upon admission, the most frequent symptoms were fever (94.5%), cough (86.4%) and dyspnea (79.1%). Diabetes mellitus (42.7%) and hypertension (33.6%) were the most common comorbidities. Regarding laboratory parameters, neutrophilia and lymphocytopenia were observed in 72.7% and 58.2% cases, respectively. The mean D-dimer (2.9 mg/l) and CRP (61.7 mg/l) levels were above their normal limits. In high resolution CT scan of the chest (HRCT chest), bilateral lung involvement was present in 85.5% cases. Ground-glass appearance was the most frequent (89.1%) radiologic pattern. Among the study subjects, empirical antibiotic, antiviral (remdesivir) drug, and systemic glucocorticoid were given to 97.3%, 83.6% and 56.4% patients, respectively. Total 15 (13.6%) patients were severely affected with COVID-19 and admitted to the ICU, requiring mechanical ventilation. During our study, 12 patients (10.9%) died either due to multiple organ dysfunction syndrome or cardio-respiratory failure. Conclusion: The study provides key information about clinical characteristics and general management of COVID-19 patients, which may help physicians to identify the factors associated with adverse outcomes in this disease. Mediscope 2022;9(1): 9-15